Condições pluviométricas extremas determinam a predominância de guildas tróficas de copépodes (Crustacea, Copepoda) em uma planície de inundação Neotropical?. - Lino, Lenin Medeiros de Almeida (2016)
We evaluated the hypothesis that intense weather events along with their variability in environmental conditions and food resources in each period (dry and wet) are crucial to the predominance of trophic guilds of herbivores and omnivores copepods in the floodplain. Also expected to: i) in the dry season, the two guilds will dominate the environment, due to the increase of phytoplankton biomass in the water column, and ii) in the rainy season, the trophic guild omnivorous copepods will prevail the environment due to reduced phytoplankton biomass to herbivores. Sampling of copepods were conducted in 9 environments of the Upper Paraná River floodplain, during the years 2000 and 2010. In those years there were climatic events La Niña and El Niño, respectively. The classification of Copepoda in two trophic guilds was made from the type of food ingested by organisms, Cyclopoida being considered omnivores and herbivores Calanoida. In order to verify differences in environmental characteristics over the years and periods of study took place a Principal Component Analysis (PCA). To test the hypothesis predominance of a particular guild trophic at different periods of years and study assessed the relationship between the abundance of each species of settings and environmental variables through multiple regression analysis. The results of Principal Component Analysis (PCA) revealed that the environmental conditions were different in the years and periods, but with a strong selection for environmental productivity variables. The regression results determined that the herbivorous copepods were significant throughout the year 2000 and the drought of 2010. The omnivores were not significant for any year and period studied. High efficiency in obtaining food in locations with poor connectivity meant that herbivores respond partially positively the first prediction in which the two guilds would benefit from the increased availability of phytoplankton biomass. The second prediction was not significant because omnivores during extreme events may have been influenced negatively by predation, migration and/or reproduction.